Gamification of learning obesity - Pang, Qing Sen (2024)
Obesity is a widespread problem worldwide, the issue is rapidly increasing in more and more countries, including both developed and developing nations, such as China, the United States, and Malaysia. It is essential to educate people about obesity early to prevent its progression and development of the obesity. Gamification is a powerful tool that can help people in this situation as it encourages to learn new things in an entertaining and exciting way. The central tenet of the project is gamification’s use in teaching players about the impact of obesity on their characters. The project will start with a thorough review of the current state of gamification in broad areas and a search for the most appropriate ways to transfer the necessary game elements to our product. The game elements that attract players do not necessarily convey knowledge as well. This ensures that the selected game elements should be not only suitable for attracting players but also effective in knowledge implementation. After the extensive analysis and design phases, the next stage of the project involves the implementation, where our ideas are put into reality through coding and subsequent testing. Once the game has been developed, tested, and validated, it will be deployed to Windows operating system, where people can obtain it for their own use.